2010
DOI: 10.1039/c003567j
|View full text |Cite
|
Sign up to set email alerts
|

Inelastic neutron scattering of Na-zeolite A with in situ ammoniation: an examination of initial coordination

Abstract: The detection and rationalization of the coordination of low concentrations of ammonia within Na-zeolite A is carried out by the application of inelastic neutron scattering (INS), using inverse geometry time of flight spectrometry to study the partial phonon density of states of in situ ammoniated Na-zeolite A. The experimental spectra are subsequently characterised by density functional calculations, incorporating pre-optimisation by geometric simulation. We find that at a concentration of four ammonia molecu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 41 publications
(42 reference statements)
0
5
0
Order By: Relevance
“…Our previous studies have shown that even low levels of ammonium exchange in zeolites lead to visible changes in INS spectra. [37][38][39]…”
Section: Resultsmentioning
confidence: 99%
“…Our previous studies have shown that even low levels of ammonium exchange in zeolites lead to visible changes in INS spectra. [37][38][39]…”
Section: Resultsmentioning
confidence: 99%
“…For example, K-A is commonly used in the ethanol drying processes [11] and partially-exchanged K/Na-A is used to separate CO 2 from CO 2 /N 2 dry mixtures [12]. Ca-A zeolites are important in industry, where they selectively adsorb linear alkanes from a mixture of branched alkanes [13], and Na + /NH 4 + exchange is useful in minimising environmental pollution and eutrophication [14][15][16][17]. Li-A was proposed as a possible delivery material for pharmacological studies [18].…”
Section: Introductionmentioning
confidence: 99%
“…Hydrogen atoms have a particularly high neutron scattering cross section (80 barns), and thus the technique is well suited to detecting hydrogen-containing adsorbates . The technique has been used successfully to observed hydrogen-containing surface species including hydrides, , peroxides, and NH 3 . , We use INS to interrogate the surface species (e.g., hydrides, NH x , ...) generated on a supported Ni catalyst after plasma treatments with N 2 and H 2 . Ni was chosen because it is inactive for thermal ammonia synthesis at 200 °C and ambient pressure but has been shown in previous studies to have appreciable NH 3 production rates under plasma stimulation. ,, …”
mentioning
confidence: 99%